2021
DOI: 10.3390/cancers13040838
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cell-Free DNA Methylation Profiles in the Early Detection of Ovarian Cancer: A Scoping Review of the Literature

Abstract: Epithelial ovarian cancer is the most lethal gynecologic malignancy and has few reliable non-invasive tests for early detection or diagnosis. Recent advances in genomic techniques have bolstered the utility of cell-free DNA (cfDNA) evaluation from peripheral blood as a viable cancer biomarker. For multiple reasons, comparing alterations in DNA methylation is particularly advantageous over other molecular assays. We performed a literature review for studies exploring cfDNA methylation in serum and plasma for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
0
11
0
1
Order By: Relevance
“…However, these data suggest that serum/plasma cfDNA methylation assays can achieve a robust diagnostic accuracy in EOC (with a median of 85% and a range of 40–91%), especially when multiple genes are used, and ovarian tumors are compared to benign pelvic masses. However, even here it is necessary to optimize the range of possible gene targets and techniques, and to include more early-stage EOC samples [ 166 ].…”
Section: Strategies For the Early Detection Of Epithelial Ovarian Cancer (Eoc)mentioning
confidence: 99%
“…However, these data suggest that serum/plasma cfDNA methylation assays can achieve a robust diagnostic accuracy in EOC (with a median of 85% and a range of 40–91%), especially when multiple genes are used, and ovarian tumors are compared to benign pelvic masses. However, even here it is necessary to optimize the range of possible gene targets and techniques, and to include more early-stage EOC samples [ 166 ].…”
Section: Strategies For the Early Detection Of Epithelial Ovarian Cancer (Eoc)mentioning
confidence: 99%
“…Recent studies showed steady improvements in diagnostic accuracies using circulating cell-free (cf)DNA resulting from genetic mutations, copy number alerations, allelic imbalance, and promoter methylation in tumors [65]. Using subgroup analyses and metaregression analyses of systematic reviews suggested that epigenetic markers (i.e., epigenetic DNA modifications, methylation, and alterations) are particularly more effective over other quantitative detection methods of cell-free (cf)DNA and RNA concentrations or chromosomal instability [65,66]. Many susceptibility genes in hereditary ovarian carcinomas are known to alter homologous recombination (HR)/DNA repair pathways [67,68], and recent genomic/epigenomic studies indicated that EOC represents a genetically heterogeneous and complex group of diseases [67][68][69].…”
Section: Molecular Markers For Surveillance Of Eocsmentioning
confidence: 99%
“…Approximately 15~20% of EOCs occur in a familial context with a high penetrant autosomal dominant genetic predisposition. To increase EOC patient survival, application of biomarkers for early diagnosis/detection and risk factor prediction, including genomic/epigenomic variants, copy number aberrations (CNAs), and DNA methylation in EOC surveillance are promising [66,70]. Moreover, due to rapid developments in DNA sequencing technology, various novel germline mutations have also been identified in familial EOC cases and in patients with early-onset EOC.…”
Section: Molecular Markers For Surveillance Of Eocsmentioning
confidence: 99%
“…DNA methylation changes are known to occur in multiple locations throughout the genome and thus have lower detection limits compared to mutation or protein marker assays. Indeed, relevant methylation changes that occur in cancer tend to be rare in normal cells 10 . Quantitation of circulating cfTDNA has been evaluated as a diagnostic approach for OC, however systematic reviews suggest the superiority of epigenetic markers over circulating cfTDNA quantitation 11 .…”
mentioning
confidence: 99%
“…A limitation of current DNA methylation analysis of cfTDNA in ovarian cancer is the focus on single or a small number of target genes previously identified to be involved in cancer pathogenesis 10 which limits diagnostic precision. In this preliminary study, we performed genome wide methylation analysis of cfDNA for the minimally invasive detection of OC.…”
mentioning
confidence: 99%